Work of meaning in the proverbs of Sheikh Mohammed Khal - Hawez, Asst. Prof. Dr. Srwsht Jawhar; Raouf, Asst. Prof. Dr. Luqman (Sulaimani Journal for Humanities, 2023)
Folklore or popular literature is considered an independent science and has a strong position in the study of the folklore of nations. The proverb occupies an important place in folklore studies, because it is a cultural heritage and the cultural background of peoples and can never be abandoned, and it has many different agendas and different and general meanings...etc. The proverb is considered an integral part of the popular heritage that members of society circulate generation after generation through oral narration, and it is the living and moving memory of the people, because it receives cultural remnants orally, and circulates them generation after generation, preserving them in the collective memory, and this is the reason that ensures their immortality. Between groups of society. This research works on the functions of proverbs in general and their function, which has become the essence of meanings and connotations in the proverbs of Sheikh Muhammad al-Khal, while identifying the types of proverbs according to the classification defined by Rudolf Solheim. It also discusses the concept of proverbs, their definition and development along with their purpose and importance. In addition, according to ancient culture, the types of proverbs were identified, which generally find themselves in standard proverbs (prose, poetic, philosophical, etc.).
Keywords: Proverb; meaning; role; agenda; education